Palaeogeographic reconstruction of the Main Harbour of the ancient city of Delos (Greece) - Desruelles, Stéphane (2023)
Delos Island, located in the Aegean region, became a major religious, cultural, and commercial hub during the Hellenistic period (323-30 BCE). From the 3rd century onwards, the island underwent significant growth, driven by the efforts of the independent city of Delos. This growth further intensified when Rome designated Delos as a free port and transferred its control to Athens in 167 BCE. The island's prosperity led to its maritime infrastructure, particularly the Main Harbour, playing a crucial role in trade. The current coastal landscape, however, bears little resemblance to the Hellenistic one. An interdisciplinary (archaeology, geomorphology, geophysics, sedimentology, micropalaeontology, and oceanography) study was conducted from 2007 to 2017 to propose a new reconstruction of the Hellenistic harbour. The study showed that the bay of the Main Harbour extended less to the north than indicated in previous studies, and that the landscape evolved considerably during Antiquity. The absence of evidence for quays suggests that access was limited to flat-bottomed boats, raising questions about the anchorage possibilities for larger boats.